Paciente de sexo masculino de 17 años de edad con epilepsia y accidente cerebrovascular. - Reyes Rodríguez, Johanny Olinda (2020)
In the present case, it refers to a 17-year-old male patient with epilepsy since birth and a cerebrovascular accident (CVA) due to a traffic accident, patient presents seizures, attends consultation due to a clinical picture of 24 hours of characterized evolution by seizures in repetitive number of 5 in 24 hours. The doctor orders an electroencephalogram, hematic biometry, and biochemical tests, performs the physical examination, shows motor deficit, does not present meningeal signs, isochoric non-reactive pupils, depressible soft abdomen, is hospitalized for due follow-up for the results obtained, the neurologist is consulted to seek adequate treatment and the nutritionist for presenting malnutrition. The nutritionist performs nutritional assessment: anthropometric, biochemical, and plans a ketogenic diet. patient measures 174 centimeter (cm), I have a weight of 54 kilogram (kg), the indices are applied in the anthropometric assessment: height for age, body mass index for age, according to the biochemical results the patient presents hyperglycemia of 112 mg / dL, hematic results show a hemoglobin of 12 g / d, and malnutrition (BMI / AGE <2 SD). Neurological diseases are an important cause of morbidity and often lead to alterations at the level of consciousness and nutritional implications due to difficulties related to food intake, such as malnutrition, anemia, etc., which merit adequate nutritional assistance based on the available scientific evidence of the case is included as a dietary treatment ketogenic meal plans.